IMPACTS OF HOME MOSQUITO VECTOR CONTROL AND INSECTICIDE TREATED NETS ON MALARIA STATUS AMONG PREGNANT WOMEN ATTENDING ANTENATAL CARE AT POLICE HOSPITAL, DUTSE, JIGAWA STATE - Mohammed, Aishat Omowumi; Ihemanma, Chioma Ada; Mansur, Murtala Musa; Jameelah, Annas Musa; Ibrahim, M. P.; Adeniyi, Kamoru Abdulazeez; Haris, N. G.; Hafizu, M.; Jibril, M. S. (FUDMA JOURNAL OF SCIENCES, 2025)
Malaria remains a critical public health challenge, particularly among vulnerable populations such as pregnant women in endemic regions. This study investigated the impact of home mosquito vector control and insecticide-treated nets (ITNs) on malaria prevalence among 50 pregnant women attending antenatal care at the Police Hospital, Dutse, Jigawa State, Nigeria. Participants' demographic characteristics, knowledge, attitudes, and practices regarding mosquito control were assessed, alongside malaria prevalence across age, marital, trimester, educational, and occupational categories. Findings revealed a malaria prevalence of 46%, with younger participants (18–24 years) and unemployed individuals showing higher rates, though statistical associations were insignificant (p > 0.05). Knowledge of malaria transmission was universal (100%), and ITN ownership was high (94%), yet only 86% reported consistent nightly use. Despite positive perceptions of ITNs, gaps in equitable distribution and consistent usage were identified, with 60% of ITNs purchased rather than obtained through free programs. Additionally, while 70% of participants engaged in regular mosquito control practices, community-based programs were limited, with only 18% reporting active initiatives in their areas.  The study underscores the need for strengthened malaria prevention strategies, emphasizing universal access to ITNs, community-driven mosquito control programs, and targeted health education campaigns. Comprehensive approaches integrating antenatal care services and public health outreach can enhance protective measures for pregnant women, mitigating malaria's impact on maternal and fetal health.
Keywords: Malaria; Mosquito vector; Insecticide-Treated Nets; Transmission